Cumulative Incidence of a Subsequent Surgery After Stress Incontinence and Pelvic Organ Prolapse Procedure - Wu, Jennifer M. (Obstet Gynecol, 2017)
OBJECTIVE: To assess the 5-year risk and timing of repeat stress urinary incontinence and pelvic organ prolapse procedures. METHODS: We conducted a retrospective cohort study, using a nationwide database, the 2007–2014 Marketscan Commercial Claims and Encounters and Medicare Supplemental Databases (Truven Health Analytics), which contain de-identified health care claims data from approximately 150 employer-based insurance plans across the United States. We included women aged 18–84 years and used CPT codes to identify surgeries for stress urinary incontinence (SUI) and pelvic organ prolapse (POP). We identified index procedures for SUI or POP after at least three years of continuous enrollment without a prior procedure. We defined three groups of women based on the index procedure: 1) SUI surgery only, 2) POP surgery only, 2) Both SUI+POP surgery. We assessed the occurrence of a subsequent SUI or POP procedure over time for women < 65 years and ≥ 65 years with a median follow-up time of 2 years (IQR 1,4). RESULTS: We identified a total of 138,003 index procedures: SUI only n=48,196, POP only n=49,120, and both SUI+POP n=40,687. The overall cumulative incidence of a subsequent SUI or POP surgery within 5 years after any index procedure was 7.8% (95%CI: 7.6, 8.1) for women < 65 and 9.9% (95%CI: 9.4, 10.4) for women ≥ 65 years. The cumulative incidence was lower if the initial surgery was SUI only and higher if an initial POP procedure was performed, whether POP only or SUI+POP. CONCLUSIONS: The 5-year risk of undergoing a repeat SUI or POP surgery was < 10%, with higher risks for women ≥ 65 years and for those who underwent an initial POP surgery.